Management of a complex intracranial arteriovenous malformation with gamma knife radiosurgery: A case report with review of literature. (March 2018) - Bir, Shyamal C.; Konar, Subhas K.; Patra, Devi P.; Maiti, Tanmoy K.; Minagar, Alireza; Nanda, Anil
Highlights: This is a unique case of early cyst formation after radiosurgery in a patient with AVM. Resection of the cyst along with AVM would be the best approach to treat this patient. Embolization before radiosurgery is not a good strategy to manage a complex AVM. Abstract: The risks and benefits of arteriovenous malformation (AVM) treatment should be considered cautiously in each patient since management strategy of it depends on various factors including age of the patient, location and volume of AVM and presence of other vascular abnormalities. Current management options of AVM include observation, endovascular embolization, radiosurgery and microsurgical resection or in combination of any two of the above procedures. Here, we have discussed a case of intracranial AVM with radiation induced early cyst formation, and performed a literature review to determine the optimum treatment of complex intracranial AVM. Standard search strategies were performed in PubMed/Medline using appropriate terms such as "intracranial arteriovenous malformation" radiosurgery, embolization and microsurgical resection as well as medical subject headings. The particular case in this study was retrospectively reviewed. Literature review revealed that the mean marginal radiation dose used by the different authors was 19 Gy, cysts were developed in 3.6% patients, the average time to form cyst was 6.6 years, average volume of cyst was 6.7 ml and maximum cysts were removed by resection. In our case, the cyst was developed 2.5 years after radiosurgery. Radiation induced cyst formation is a delayed complication of AVM management. However, cyst formation in this case was comparatively earlier in our case. Therefore, continuous follow-up after radiosurgery is required for early detection of cyst formation. In addition, the review revealed that embolization before radiosurgery was a poor strategy.